Old structures versus new logic in the electronics industry - Jörg Meyer-Stamer (Intereconomics, 1995)
Electronics is a branch of industry in which the competitive position of European firms is relatively weak, compared to the chemical, motor vehicle and mechanical engineering industries. This fact appears to some observers—in view of the electronic industry's high rates of growth and its technologically “strategic” importance—to represent a threat to Europe's future industrial development. This has led to intensive political discussions in recent years and to a multitude of initiatives for the revitalisation of the European electronics industry. This paper analyses the extent to which the discussions and initiatives have in fact dealt with the problems in hand.
Keywords: 330